Construção “mas” : motivações conceptuais e produtividade de uso - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This research aims to analyze and describe the construction but in a constructional perspective in synchronic uses of Brazilian Portuguese (PB), with a focus on the variant spoken in Goiás. Prototypically this construction meets the counterjunction subsystem, Or.1 but Or. 2, for making the connection between independente sentences syntactically and semantically independent sentences in an opposition relationship. The analyzed corpus consists of data from the Fala Goiana Project (FG). Initially we performed the selection and quantification of the various uses of but in prototypical uses such as adversative conjunction and in discursive uses. Among these, focusing on analysis of uses of intensifying and smoothing effects From this point of view, the hypothesis was raised that the but is a micro-construction that regulates a significant textual load acting both at the inter-organizational level promoting coordination relations, and at the discursive level, assisting in the production of the effects of meaning. In the analysis, we seek to understand to what extent and what conceptual motivations this construction is being recruited by the speakers of Goiás in these specific discursive uses. This research is based on the theories of Usage-based Linguistics (Usage-based linguistics), principles of classical Functionalism, Cognitive Linguistics and especially the Grammar of Constructions. In the construction analysis we used Bybee (2003, 2010, 2016), Goldberg (1995, 2006), Traugott and Trousdale (2013), in addition to Croft (2001), Croft and Cruse (2004), Langacker (1987), Fauconnier (1994, 1997), Hopper and Traugott (2003), Neves (1984, 1997, 2010, 2011, 2018 a,b,c) and others. The discursive uses found showed that microconstruction goes through a process of change due to its removal in degrees from the prototypical category.
Construction "but" : conceptual motivations and productivity of use
Keywords: Microconstrução - mas; Discurso; Mudança; Microconstruction - but; Speech; Change; LINGUISTICA, LETRAS E ARTES